2018
DOI: 10.1158/1541-7786.mcr-17-0593
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Positively Regulates YAP and TAZ in Mammary Tumorigenesis Through Multiple Signaling Pathways

Abstract: Breast cancer is a leading cause of death in women worldwide. Active mutations of PI3K catalytic subunit PIK3CA (e.g., H1047R) and amplification of its homolog PIK3CB are observed in a large number of breast cancers. In recent years, aberrant activation of Transcriptional coactivator with PDZ binding motif (TAZ) and its paralog Yes-associated protein (YAP) have also been found to be important for breast cancer development and progression. However, whether PI3K interacts with YAP/TAZ during mammary tumorigenesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 47 publications
1
44
1
Order By: Relevance
“…Our in silico analysis revealed that many of our miRNAs associated with OS and RFS target components of the hippo signaling pathway. More specifically, we found that miR-30a targets the effector protein YAP, an oncogene commonly dysregulated in cancer and linked to poor prognosis in breast cancer (78)(79)(80)(81). With the use of qRT-PCR, we reveal an inverse relationship between miR-30a and YAP in human normal (MCF-10A) and TNBC (MDA-MB-231) cells and show that overexpression of miR-30a in MDA-MB-231 cells significantly downregulates YAP to levels characteristic of MCF-10A cells.…”
Section: Discussionmentioning
confidence: 93%
“…Our in silico analysis revealed that many of our miRNAs associated with OS and RFS target components of the hippo signaling pathway. More specifically, we found that miR-30a targets the effector protein YAP, an oncogene commonly dysregulated in cancer and linked to poor prognosis in breast cancer (78)(79)(80)(81). With the use of qRT-PCR, we reveal an inverse relationship between miR-30a and YAP in human normal (MCF-10A) and TNBC (MDA-MB-231) cells and show that overexpression of miR-30a in MDA-MB-231 cells significantly downregulates YAP to levels characteristic of MCF-10A cells.…”
Section: Discussionmentioning
confidence: 93%
“…Intriguingly, we also observed enrichment of PIK3CA mutant (p=0.0003) among OSCC lines that are compensable for YAP1 or WWTR1. As recent studies have provided evidence that YAP1 and WWTR1 could mediate mutant PIK3CA-induced tumorigenesis ( Zhao et al, 2018 ) andother studies also suggested crosstalk between these Hippo pathway effectors with the PI3K-Akt pathway ( García-Escudero et al, 2018 ), confirmatory and mechanistic studies will be needed to delineate why YAP1 and WWTR1 function can be compensated in these PIK3CA -mutated cell lines, while distinct dependencies on either paralog are observed in PIK3CA wild-type lines. The functional loss of mutated FAT1 has also been reported to be associated with YAP1 activation in head and neck cancer ( Martin et al, 2018 ), however, no enrichment of FAT1 mutation was seen among the YAP1-dependent nor WWTR1-dependent models in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 169 ] Recent evidence suggests that PI3K‐Akt signaling also inhibits the Hippo pathway to promote YAP/TAZ activation to drive cell proliferation and malignancy. [ 99,115,170‐178 ] Importantly, further work is necessary to identify the molecular mechanism by which PI3K‐Akt signaling inhibits the Hippo pathway. In addition, while PI3K‐Akt signaling appears necessary to promote YAP/TAZ activation, it is apparently not sufficient, as cells also require mechanical stimulation or other additional inputs to activate YAP/TAZ.…”
Section: Introductionmentioning
confidence: 99%
“…Specific inhibitors of PI3K and AKT are in clinical trials for cancer therapy. [ 169 ] Treatment of cancer cells with these inhibitors decreases YAP/TAZ nuclear translocation and activity, [ 170,172,173,176 ] suggesting a possible mechanism by which these inhibitors may reduce cancer growth and progression. Complete inhibition of YAP/TAZ in tumors may require dual inhibition of both PI3K‐AKT and SRC signaling.…”
Section: Introductionmentioning
confidence: 99%